IMPLEMENTASI MODEL PROJECT BASED LEARNING BERBASIS ETNOMATEMATIKA RUMAH KAJANG LAKO PADA MATERI BANGUN RUANG DAN SKALA UNTUK MENINGKATKAN LITERASI NUMERASI SISWA KELAS V SD - Dewi Fitriani; Irfan, Muhammad Khidayatullah; Siti Maisarah; Violita Zahyuni; Febriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of numeracy literacy among elementary school students remains a major issue in mathematics learning, particularly in topics related to three dimensional shapes and scale, which tend to be abstract and lack contextual relevance. One effort to address this issue is the implementation of meaningful and contextual learning rooted in local culture. This study aims to improve the numeracy literacy of fifth-grade elementary school students through the implementation of an ethnomathematics-based Project-Based Learning (PjBL) model integrating Rumah Kajang Lako in the topics of three-dimensional shapes and scale. This study employed Classroom Action Research (CAR) using a mixed-methods approach, conducted in two cycles through the stages of planning, action implementation, observation, and reflection. The research subjects were students of class V B at SD Negeri 34/1 Teratai Muara Bulian. Data collection techniques included numeracy literacy tests, observation of student activities, student response questionnaires, interviews, and documentation. Quantitative data were analyzed using percentages of learning mastery and improvement in learning outcomes, while qualitative data were analyzed through data reduction, data presentation, and conclusion drawing with triangulation of techniques and sources. The results indicate that the implementation of the ethnomathematics based PjBL model integrating Rumah Kajang Lako significantly improves students’ numeracy literacy, both in quantitative and spatial competencies. In addition, students’ responses to the learning process demonstrate increased learning motivation, collaboration skills, mathematical modeling abilities, and positive learning reflection. Therefore, the ethnomathematics-based PjBL model integrating Rumah Kajang Lako is effective as an alternative contextual learning approach to enhance numeracy literacy among elementary school students.